Pembelajaran E-Learning Berbasis Schoology - Suchaina Suchaina (FKIP Universitas Islam Jember, 2018)
The development of knowledge and technology nowadays has reached all aspects of life including education field. The digital learning invites the lecturers to be able to apply the system of E-learning as the use of technology development. One of E-learning application in education is schoology. Schoology has some interesting teaching and learning features like groups, resources, courses, quiz and attendance. The difference between the usual teaching and learning process with E- learning is from the centered of the activity, usual class is lecturer-centered the but e-learning is student-centered. E-learning will invite the students to be active in the learning process and try to find the materials they need initiatively. Keywords: E-learning, Schoology